Investigating the Impact of Work Family Conflict, Job Stress on Innovative Work Behavior with Job Satisfaction as a Mediator on University Women Teacher in Indonesia: Supporting SDG 4 - Lilik Nurcholidah; Tulus Haryono; Sinto Sunaryo; Hidajat Hendarsjah (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: The increasing complexity of academic responsibilities requires university teachers to continuously develop innovative work behavior to improve educational quality. However, work-family conflict and job stress may become barriers that reduce educators’ ability to contribute innovative practices in higher education. This study aims to investigate the impact of work-family conflict and job stress on innovative work behavior with job satisfaction as a mediating variable among university women teachers in Indonesia. This study contributes to SDG 4 (Quality Education) by emphasizing the importance of educator well-being and innovation capacity in strengthening educational quality. Method: A quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The research sample consisted of 260 university women teachers from ten private universities in Indonesia selected using a snowball sampling technique. Data were collected using instruments measuring work-family conflict, job stress, job satisfaction, and innovative work behavior. Data analysis was performed using SmartPLS 3. Results: The results indicate that work-family conflict and job stress have negative and significant effects on innovative work behavior. Furthermore, work-family conflict and job stress negatively affect job satisfaction, while job satisfaction has a positive and significant influence on innovative work behavior. Job satisfaction also significantly mediates the relationship between work-family conflict and job stress on innovative work behavior. Novelty: The study provides new insights into the importance of improving educators’ psychological well-being and job satisfaction as strategies to encourage innovative behavior among university teachers. These findings support SDG 4 by highlighting the role of teacher capacity development in achieving sustainable and high-quality education.